Deteksi Dini Krisis Keuangan di Indonesia: Determinan Makro Ekonomi tahun 1996-2013 - Erbaviantha, Brigita Vegy (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
The aim of this study is to analyze the determinants that affect the financial crisis in Indonesia. The determinants were Real Exchange Rate, foreign reserves growth, net export-import, lending and deposit ratio, world oil price. This study using descriptive analysis. The results showed that Real Exchange Rate, foreign reserves growth, net export-import, lending and deposit ratio, world oil price had a effect on financial crisis in Indonesia. The recommendation of this study is government need to develop an early warning system with the appropriate approach to economy condition of Indonesia in order to avoid the wider financial crisis.Keywords : Financial Crisis, Real Exchange Rate, foreign reserves growth, net export-impor, lending and deposit ratio, world oil price.